How Organizations Change: Three Mechanisms Supporting the Incorporation of Emerging Strategies in U.S. Higher Education - Ventresca, M; Washington, M (2004)
This paper develops the argument that institutional mechanisms support changes in organizational strategies in ways that contrast with the standard interpretation of institutional “iron cages” that pressure organizations to conform. We specify three institutional process mechanisms that support organizational change” dominant logic-consistent activity, external charters, and peer emulation” and we test these claims with longitudinal data on the emerging strategies in early U.S. intercollegiate athletics. We argue that the supporting institutional mechanisms affect the incorporation patterns of intercollegiate programs in basketball, ice hockey, and lacrosse over the period from the late nineteenth century to the present. The research strategy of examining the spread of three different sports programs, each a proxy for different strategies of resources and visibility, provides evidence on the comparative pattern of effects of the three institutional mechanisms. Results indicate that all three institutional support mechanisms affect the incorporation of the intercollegiate programs. Differences in the pattern of incorporation across the three strategies provide robust evidence for alternatives to a prevailing “iron cage” view of institutional pressures and constraints. These findings also reinforce the importance of specifying field-level mechanisms to supplement a focus on organization-level mechanisms.